Method Development and Validation of Stability Indicating Method for Assay of Diacerein and Aceclofenac by High Performance Liquid Chromatography - A. Badgujar, Madhukar; V. Mangaonkar, Kiran (Asian Journal of Chemistry, 2011)
A simple, fast, precise, specific, accurate and stability-indicating reversed phase high performance liquid chromatographic (HPLC) method was developed and validated for the simultaneous determination of diacerein and aceclofenac in tablets. The column used was Inertsil ODS 3V C18, 250 × 4.6 mm, i.d. 5 μm and a mobile phase composed of methanol:acetonitrile:buffer (0.02 M KH2PO4) (50:20:30), pH 5.9 adjusted with 0.1 % triethylamine. The retention times of diacerein and aceclofenac were found to be 3.2 and 6.2 min, respectively. Linearity was established for diacerein and aceclofenac in the range of 20-100 μg/mL and 40-200 μg/mL, respectively. The percentage recoveries of diacerein and aceclofenac were found to be in the range of 99.99 to 101.34 % and 97.90 to 100.35 % respectively. Both these drugs were subjected to acid, alkali, oxidation and thermal degradation. The degradation study shows 22.58 and 13.49 % degradation for diacerein and aceclofenac respectively, under alkali degradation condition. The degradation products of diacerein and aceclofenac were well resolved from the pure drug with significant differences in their retention time values. This method can be successfully employed for simultaneous quantitative analysis of diacerein and aceclofenac in bulk drugs and formulations.